Awareness of University Students on the Protection of Personal Data and the Right to Be Forgotten: A Study on Information and Document Management, Journalism and Law Departments - Şeşen, Yasin; Şeşen, Elif (Information World, 2025)
Personal data is the sum of the data produced by or for individuals. As defined in Article 2 of the EU General Data Protection Regulation, personal data refers to any information relating to an identified or identifiable natural person. The aim of this study is to analyze the knowledge and awareness levels of students studying at the Information and Document Management, Journalism and Law departments of Niğde Ömer Halisdemir University and Ankara University regarding the protection of personal data and the right to be forgotten. In the study, undergraduate-level departments with closely related topics were selected within the scope of the course content, and semi-structured interviews were conducted with a total of 12 students, one student from each class in three departments. The data collected in the study were subjected to thematic analysis supported by content analysis and the results obtained were interpreted. As a result of the analysis, 5 themes came to the fore: personal data, content management, awareness, education and knowledge level. The results of the study show that, in general, the participants have knowledge about the protection of personal data, but they do not reflect this in their behavior. The majority of the participating students stated that they had heard the concept of the right to be forgotten before, but did not have knowledge about this concept. The results of this study make an important contribution to the field of information and document management in general and to the literature on the right to be forgotten and the protection of personal data.